Implementation of Qur'anic Literacy at the Elementary School Level in South Sulawesi - Syakur, Abdul; Mania, Sitti; Achruh, Andi; Haddade, Hasyim (Formosa Journal of Multidisciplinary Research, 2024)
The aim of this research is to reveal the implementation of Al-Qur'an literacy at elementary school level in South Sulawesi. This type of research is classified as qualitative. The approach that researchers use in this research is a qualitative and scientific approach which includes an educational approach. Furthermore, the data collection methods used were observation, interviews and documentation. Then, data processing and analysis techniques are carried out through three stages, namely: data collection, data reduction, data presentation, and drawing conclusions. The research results show that; The implementation of Al-Qur'an Literacy at Primary School Level in South Sulawesi, based on research results, was found to have been carried out well, even in the implementation of the evaluation and follow-up stages, as for the learning models or methods used by teachers in implementing or developing al-Qur'an literacy programs. The Qur'an in elementary schools uses the Iqra' method, the Tartil method, and several other methods. Among the many types of methods used, the methods that are most often used are the iqro method combined with the tartil and memorization methods and the tilawati method combined with the BTQ tahfidz program. This method was developed and implemented based on the level of student ability, in stages each student is guided starting from Iqro' 1 to Iqro' 6 then continuing to Juz 1 to 30. Likewise, the tahfidz program starts with Juz 30, 29 and 28.